Cyclin E and Cdk2 Control GLD-1, the Mitosis/Meiosis Decision, and Germline Stem Cells in Caenorhabditis elegans - Jeong, Johan (Public Library of Science, 2011)
Coordination of the cell cycle with developmental events is crucial for generation of tissues during development and their maintenance in adults. Defects in that coordination can shift the balance of cell fates with devastating clinical effects. Yet our understanding of the molecular mechanisms integrating core cell cycle regulators with developmental regulators remains in its infancy. This work focuses on the interplay between cell cycle and developmental regulators in the Caenorhabditis elegans germline. Key developmental regulators control germline stem cells (GSCs) to self-renew or begin differentiation: FBF RNA–binding proteins promote self-renewal, while GLD RNA regulatory proteins promote meiotic entry. We first discovered that many but not all germ cells switch from the mitotic into the meiotic cell cycle after RNAi depletion of CYE-1 (C. elegans cyclin E) or CDK-2 (C. elegans Cdk2) in wild-type adults. Therefore, CYE-1/CDK-2 influences the mitosis/meiosis balance. We next found that GLD-1 is expressed ectopically in GSCs after CYE-1 or CDK-2 depletion and that GLD-1 removal can rescue cye-1/cdk-2 defects. Therefore, GLD-1 is crucial for the CYE-1/CDK-2 mitosis/meiosis control. Indeed, GLD-1 appears to be a direct substrate of CYE-1/CDK-2: GLD-1 is a phosphoprotein; CYE-1/CDK-2 regulates its phosphorylation in vivo; and human cyclin E/Cdk2 phosphorylates GLD-1 in vitro. Transgenic GLD-1(AAA) harbors alanine substitutions at three consensus CDK phosphorylation sites. GLD-1(AAA) is expressed ectopically in GSCs, and GLD-1(AAA) transgenic germlines have a smaller than normal mitotic zone. Together these findings forge a regulatory link between CYE-1/CDK-2 and GLD-1. Finally, we find that CYE-1/CDK-2 works with FBF-1 to maintain GSCs and prevent their meiotic entry, at least in part, by lowering GLD-1 abundance. Therefore, CYE-1/CDK-2 emerges as a critical regulator of stem cell maintenance. We suggest that cyclin E and Cdk-2 may be used broadly to control developmental regulators.